Employment effects of work sharing: an econometric analysis for West Germany - Viktor Steiner; Ralf-Henning Peters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
In this paper we estimate the employment effects of a reduction in weekly normal hours in West German manufacturing on the basis of an econometric models using industry panel data. We distinguish between unskilled, skilled and high-skilled workers and show that labor demand elasticities with respect to real wages differ significantly between these three skill groups. Given wages, the direct employment effect of a reduction in weekly normal hours is negligible for all three groups. However, taking the adjustment of wages into account, which compensates workers to some extent for lost income due to the reduction of working hours, the net employment effect becomes negative on average. Due to their relatively large wage elasticity, this negative effect is particularly strong for the unskilled. ?Work sharing? by means of general hours-reductions can thus not be considered an adequate policy to reduce unemployment.
Keywords: 330; Arbeitszeitflexibilisierung; Job Sharing; Humankapital; Lohnpolitik; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Deutschland